Iodinated contrast media-induced hyperthyroidism (Journal of Medical Science, 2020)
Currently, iodinated contrast media (ICM) is widely used in radiology, therefore numerous patients are exposed to contrast administration during diagnostic and interventional procedures. ICM contains an amount of iodine well above the recommended dietary allowance, which can lead to thyroid dysfunction. Indeed, individuals that are highly susceptible to increased iodine intake are often patients with pre-existing thyroid disease. ICM-induced hyperthyroidism (IIH) is usually transient, however, it may present as clinically significant thyrotoxicosis. Although IIH has been investigated in multiple studies, there is still a lack of consensus regarding prophylactic therapy of IIH and no specific guidelines. This review aimed to summarise previous literature concerning the influence of ICM exposure on thyroid status and prophylactic therapy of IIH.